Age, Residence, Parents' Educational Attainment and Exposure to Media Affect Students' Learning Styles - Elvin Balallo; Crizzle Bajet Paz (Philippine Association of Institutions for Research, Inc., 2015)
Most students are unaware of their learning styles and emotional intelligence.  Thus, it is important to know one's learning styles and emotional intelligence because they can be used to increase self-awareness as to their strengths and weaknesses as learners. The study determined the learning styles and emotional intelligence of the students in the College of Technology of University of Northern Philippines, Philippines. The study utilized descriptive-correlational method of research. Results showed that student respondents have an overall high level of learning style in all of its three dimensions: visual, auditory, and kinesthetic. Also, they have an overall high level of emotional intelligence in all of its dimensions. The overall level of learning styles of the respondents is significantly related with self-motivation while visual learning style is significantly linked to self-regulation.  Likewise, auditory learning style is significantly related to self-awareness, self-motivation, social skills and the overall level of emotional intelligence. Meanwhile, kinesthetic learning style is significantly related to social awareness and self-motivation. The university should conduct an assessment of learning preferences of the students to determine their strengths and weaknesses. Likewise, emotional intelligence tests should be given to students to provide essential data on the attitudes of these students.